Комунізація та Декомунізація топонімії Кам’янця-Подільського - Старенький, І.; Зайшлюк, Я. (Місто: історія, культура, суспільство, 2017)
У статті розглядаються зміни на топонімічній карті Кам’янця-Подільського протягом 20-х років ХХ – початку ХХІ ст., які пов’язані з процесом комунізації урбанонімів у радянський період та декомунізації в період незалежності України, у тому числі за Законом України «Про засудження комуністичного та націонал-соціалістичного (нацистського) тоталітарних режимів та заборону пропаганди їх символіки». В статье рассматриваются изменения на топонимической карте Каменец-Подольского в течение 20-х годов ХХ - начала ХХI в., связанные с процессом коммунизации урбанонимов в советский период и декоммунизации в период независимости Украины, в том числе связанный с Законом Украина «Об осуждении коммунистического и национал-социалистического (нацистского) тоталитарных режимов и запрет пропаганды их символики». The article tells about change on toponymy map in Kamyanets’-Podil’s’ky for 20 year ХХ – begin ХХІ century, what is consist of communization’s urbanonimiv in Soviet period. Within 20 years, most microtoponyms that do not fit into the ideological system of the Communist Party were renamed – it was given the name of party and military leaders of the USSR, the ideologists of the communist movement. In 30 years of these objects were renamed due to the unprecedented scale repressive movement and different kinds of executions of Soviet leaders. After the war Communization toponymy held mainly by the new street names, instead of renaming existing ones. Since the beginning of the collapse of the Soviet Union and the loss of dominance of the Communist Party ideology, starts reverse process – decommunisation. Primarily old name was returned to the historic streets of Kamyanets’-Podil’s’ky in 1990 over 1992-1995. De-communization held by renaming streets of the new city, which bore the names of communist leaders. New round of decommunisation associated with the Revolution of dignity and the Law of Ukraine «On the condemnation of Communist and National Socialist (Nazi) totalitarian propagation and ban their symbols.» During this period, toponymic objects included in the list of those subject decommunisation given new names. If the situation Kamyanets’-Podil’s’ky, streets and lanes provided the names of the dead patriots during the Revolution of dignity and Russian-Ukrainian war in Eastern Ukraine.